Prevalence of diarrhoea, and associated risk factors, in children aged 0-5 years, at two hospitals in Umuahia, Abia, Nigeria (UNED Research Journal, 2017)
Diarrhoea is the second leading cause of infectious morbidity and mortality in children under five years of age. This study aimed at identifying the most common parasites and potential risk factors for diarrhoea among children 0-5 years attending Abia State Specialist hospital and Federal Medical Centre, Umuahia, in south eastern Nigeria. We used 400 faecal samples from children with diarrhoea –and 200 without– in combination with hospital-based case control and a questionnaire Stool samples were processed with direct normal saline and formal-ether sedimentation method for parasitological studies. More males than females were infected in nearly all age groups in both diarrhoeal and control groups (X2=23.04, df=1, P
Keywords: Diarrhoea; Risk factor; Hygiene; Umuahia; Nigeria